1991
DOI: 10.1073/pnas.88.7.2835
|View full text |Cite
|
Sign up to set email alerts
|

Mouse splenic and bone marrow cell populations that express high-affinity Fc epsilon receptors and produce interleukin 4 are highly enriched in basophils.

Abstract: Splenic and bone marrow cells from normal mice, and from mice that have been polyconally activated by injection of anti-IgD antibody, contain cells that produce interleukin 4 (IL4) in response to crosslinkage of Fc, receptors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
138
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(141 citation statements)
references
References 38 publications
2
138
0
1
Order By: Relevance
“…IL-4-induced IFN-␥ production in PDCs was also observed in C57BL/6 mice (data not shown), suggesting that this phenomenon is a general one observed beyond strain differences. Because IL-4 is produced in an early phase in immune responses by NK T cells (44) and/or basophils (45,46), the IL-4-induced IFN-␥ production by PDCs may function in the negativefeedback regulation against a Th2-type deviation in an early phase of immune responses. In this regard, de Heer et al (14) have demonstrated recently that PDCs inhibit typical Th2 responses such as IgE production and allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4-induced IFN-␥ production in PDCs was also observed in C57BL/6 mice (data not shown), suggesting that this phenomenon is a general one observed beyond strain differences. Because IL-4 is produced in an early phase in immune responses by NK T cells (44) and/or basophils (45,46), the IL-4-induced IFN-␥ production by PDCs may function in the negativefeedback regulation against a Th2-type deviation in an early phase of immune responses. In this regard, de Heer et al (14) have demonstrated recently that PDCs inhibit typical Th2 responses such as IgE production and allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Upon receptor cross-linking, activated basophils rapidly release effector molecules including histamine and proteases from cytoplasmic granules. They further produce various proinflammatory lipid mediators, chemokines, and the Th2-associated cytokines IL-4, IL-5, and IL-13 (9)(10)(11). Over the past years several genetic mouse models have been used to elucidate basophil functions in vivo.…”
mentioning
confidence: 99%
“…Recent studies indicated that basophils regulate Th1/Th2 homeostasis (5,6) and humoral immunity (7). Basophils produce large amounts of IL-4, a key cytokine in Th2 skewing, in response to various stimuli, including IL-3, the protease allergen papain, and cross-linking of surfacebound IgE molecules (8,9). In addition, basophils have been shown to express MHC class II and costimulatory molecules and to function as APCs (10)(11)(12), although the role of basophils as APCs in vivo is still controversial (13)(14)(15)(16).…”
mentioning
confidence: 99%